Resident’s Quality of Life in the Context of Tourism Development: A Systematic Review - Abdillah, Fitri; Ayuningsih, Sri Fajar (Jurnal Ilmiah Hospitality Management, 2025)
This systematic review syntheses 37 peer-reviewed studies published between 2020 and 2024 to examine how residents’ Quality of Life (QoL) has been conceptualised and assessed within contemporary tourism scholarship. Using bibliometric mapping and qualitative content analysis, the review identifies six dominant thematic clusters: the built environment and destination sustainability; resident–tourist interaction and value co-creation; sustainable tourist behaviour and pro-environmental actions; social tensions and perceived tourism impacts; experience-based and representational constructions of well-being; and objective QoL measurement and community evaluation frameworks. The findings reveal a marked shift from narrow, impact-driven and monodisciplinary approaches towards more integrative, multidimensional understandings of QoL that encompass economic, social, cultural, environmental, psychological, and governance dimensions. The period also reflects a conceptual transition from viewing well-being as a static condition to interpreting it as an evolving process aligned with transformational and experience-centred tourism. The review contributes theoretically by establishing QoL as a central indicator of destination sustainability, elaborating the role of value co-creation within host–guest relations, and highlighting the influence of implicit emotions and digital representation on QoL perceptions.